Thermal dissipation performance of metal-polymer composite heat exchanger with V-shape microgrooves: A numerical and experimental study - Sun, Jingyao; Zhuang, Jian; Jiang, Hui; Huang, Yao; Zheng, Xiuting; Liu, Ying; Wu, Daming (Applied thermal engineering, 2017)
•A metal-polymer composite heat exchanger with V-shape microgrooves was proposed.•The relationship between thermal conduction flux and thickness of single layer polymer was discussed.•The governing equations of heat exchanger were established and solved by iterative solution.•Four basic design criterions were proposed based on numerical analysis results.•A self-made testing platform was established to obtain real time data in experimental study. Nowadays, power consumption and heat output problems are becoming more and more serious with the rapid development of multi-functional and high integration density systems. The installation space for heat exchangers is also getting smaller and smaller. Thus, the need for efficient thermal dissipation performance within limited space becomes one of the major topics in this field. In this paper, a new kind of metal-polymer composite heat exchanger with V-shape microgrooves is proposed. The physical model and governing equation of it are established under several suitable assumptions. The influences of some key factors (half apex angle, thermal conductivity coefficient, radiant emissivity, etc.) on thermal dissipation performance of metal-polymer composite heat exchanger are investigated by numerical computation method. Furthermore, a comparison of the thermal dissipation performances between commercial aluminum heat exchanger and metal-polymer composite heat exchanger with V-shape microgrooves is performed. Results show that although the spatial volume of metal-polymer composite heat exchanger is only one-fifth of that of aluminum heat exchanger, their thermal dissipation performance is almost the same. As metal-polymer composite heat exchanger has the advantages of high processing efficiency, low cost, light weighted and space saving, it will play an important role in the field of heat exchanger undoubtedly in the near future.